Influence of immunosuppression on seroconversion against SARS‐CoV‐2 in two kidney transplant recipients. Issue 1 (8th August 2020) - Wang, Aileen X.; Quintero Cardona, Orlando; Ho, Dora Y.; Busque, Stephan; Lenihan, Colin R.
Abstract: Solid organ transplant recipients are at risk for infectious complications due to chronic immunosuppression. The outbreak of coronavirus disease 2019 (COVID‐19) in the United States has raised growing concerns for the transplant patient population. We seek to add to the current limited literature on COVID‐19 in transplant recipients by describing the clinical course of two kidney transplant recipients with SARS‐CoV‐2 infection monitored by both RT‐PCR and serology. Through careful adjustment of their immunosuppression regimen, both patients had excellent recovery with intact graft function and development of anti‐SARS‐CoV‐2 antibodies.